Dataset for Creating Pedotransfer Functions to Estimate Organic Liquid Retention of Soils - Hernádi Hilda; Makó András (Journal of Environmental Geography, 2014)
Soil properties characterising pressure-saturation relationships (P-S), such as the fluid retention values or the fitting parameter of retention curves are basic input parameters for simulating the behaviour and transport of nonaqueous phase liquids (NAPLs) in subsurface. Recent investigations have shown the limited applicability of the commonly used estimation methods for predicting NAPL retention values in environmental practice. Alternatively, building pedotransfer functions (PTFs) based on the easily measurable properties of soils might give more accurate and reliable results for estimating hydraulic propertie s of soils and enable the utilisation of the wide range of data incorporated in Hungarian and international datasets. In spite of the availability of several well-established PTFs to predict the water retention of soils only a limited amount of research has been done concerning the NAPL retention of soils. Thus, in our study, data from our recent NAPL and water retention mea surements were collected into a dataset containing the basic soil properties as well. Relationships between basic soil propert ies and fluid retention of soils with water or an organic liquid (Dunasol 180/220) were investigated with principal component analysis. NAPL retention of soil samples were determined with PTFs, based on basic soil properties and their d erived values, and using a scaling method. Result of the statistical analysis (SPSS 13.1) revealed that using PTFs could be a promising alte rnative and could give more accurate results compared to the scaling method both for determining the NAPL saturation or the volumetric NAPL retention values of soils.